(3cJGH aj SQ GdMQhas ((3OeTb s)
(3ChdgG (B:s
(3eG jYHQ Yfg GdjGA ef JfRdgG Ch JWhQgG aChdg eJfRd Ohf eG jYHQ Yfg ef eYfGg s
(3BNQgG (B:s
(3hbO PcQfG ef HYV eG jYWjg MbGFb GdMQcGJ eG jdjb HgPG GdcJGH hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jdjg TQM dHYV CHjGJ ai SQ GdMQha s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMQha h GdChaGbs